2014
DOI: 10.1108/ijmpb-09-2013-0048
|View full text |Cite
|
Sign up to set email alerts
|

Understanding project success through analysis of project management approach

Abstract: Purpose – The purpose of this paper is to show that project success is dependent on the project management approach selected, relative to the challenges posed by the project, and to develop an analytical model for analyzing the performance of the project organization. Design/methodology/approach – The research is based on literature review, model development, interviews, and case studies. Finding… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
43
0
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 79 publications
(56 citation statements)
references
References 22 publications
2
43
0
4
Order By: Relevance
“…International Journal of Managing Projects in Business 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Earlier studies have revealed that project success can be endangered if the startup is not properly performed (Ahonen, Savolainen 2010, Rolstadås, Tommelein et al 2014). In addition, the boundaries for the supplier's software development project startup phase have been defined, and action points in the project start-up process have been identified .…”
Section: Page 19 Of 32mentioning
confidence: 99%
“…International Journal of Managing Projects in Business 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 Earlier studies have revealed that project success can be endangered if the startup is not properly performed (Ahonen, Savolainen 2010, Rolstadås, Tommelein et al 2014). In addition, the boundaries for the supplier's software development project startup phase have been defined, and action points in the project start-up process have been identified .…”
Section: Page 19 Of 32mentioning
confidence: 99%
“…If a company chooses and builds good projects, it could increase its revenues, decrease life cycle costs, and use less capital to achieve its business goals (Lavingia, 2003). The project management process relies primarily on project plans, as the project plans represent the scope of work that will be achieved through the plan (Rolstad°as, Tommelein, Schiefloe, & Ballard, 2014).…”
Section: Project Management Processmentioning
confidence: 99%
“…Topical issues of management in construction and in the course of construction projects implementation are considered in modern scientific and business literature [1][2][3][4][5][6]. Considerable attention is paid to specific features of implementation of construction projects in different segments of real estate markets (hotel, retail, office facilities, etc.…”
Section: Introductionmentioning
confidence: 99%